Green infrastructure optimization to achieve pre-development conditions of a semiarid urban catchment. Issue 6 (29th April 2019) - Tavakol-Davani, Hessam E.; Tavakol-Davani, Hassan; Burian, Steven J.; McPherson, Brian J.; Barber, Michael E.
Abstract : The introduced hydrologically comprehensive green infrastructure design approach exceeds conventional stormwater runoff reduction goals in terms of common environmental benefits. Abstract : One challenge facing sustainable cities is managing stormwater in urban catchments. Of particular interest is mitigating the negative impacts of urbanization on hydrologic variables to a sustainable level. In this context, "sustainable" could be defined as mimicking the pre-development conditions (PDC) of an urban catchment by implementing green infrastructure (GI). Nevertheless, common stormwater management standards do not necessarily maintain the PDC of a region. They often prioritize site suitability and reduction of runoff volumes that can be used to partially meet the PDC of the area. However, a goal could be to get closer to PDC in maximum extent possible, in all hydrologic variables, not just runoff; following the primary purpose of designing GIs. Although studies show GI techniques can significantly contribute to approaching PDC, no comprehensive methods incorporate multiple hydrological components and reveal compatible types of GI with the PDC of a catchment. To introduce a comprehensive GI design approach based on PDC nearness, a systematic Multi-Objective Optimization (MOO) framework was developed and is presented in this paper. This framework employs the recently introduced PDC nearness metric known as water budget restoration coefficient (WBRC), and includes comparison of two different sets of tradeoffs based on two independent optimization sets: (i) the first optimizes candidate GIs in terms of life cycle cost (LCC) and runoff volume (RV), and represents common practice, and (ii) the second one optimizes GIs in terms of LCC and WBRC, representing a more comprehensive hydrologic goal. The selected candidate GIs were i) permeable pavements (PP), (ii) green roof (GR) and (iii) bio-retention cells (BC), because of their diverse hydrological benefits. The optimum results of the two MOO sets were compared in terms of environmental and stormwater management benefits to reveal the overall performance of both approaches. The results suggest that considering WBRC criteria in the optimization process outperforms conventional practice in terms of common benefits. Specifically, 50% more evapotranspiration, which can be translated to having more plants and eventually better air quality; 30% more reduction in the duration of flood events; 2% more total suspended solids removal; and about the same level of performance in groundwater recharge and flood volume reduction.